Helicobacter pylori Infection in European Children with Gastro-duodenal Ulcers and Erosions - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
Background: To analyze risk factors associated with gastro-duodenal ulcers and erosions in children. Methods: Open, prospective, multicenter, case-control study carried out in 11 European countries in patients with gastric or duodenal ulcers/erosions and 2 age-matched controls each. Possible risk factors were recorded. Logistic regression models were performed with adjustment for centers and age groups. Results: Seven-hundred thirty-two patients (244 cases, 153 with erosions only and 91 with ulcers, and 488 controls) were recruited. Children receiving antimicrobials or acid suppressive drugs before endoscopy were excluded (202 cases/390 controls remained for risk factor analysis). Helicobacter pylori was detected more frequently in cases than controls but only in 32.0% versus 20.1% in controls (P = 0.001). Independent exposure factors for gastric ulcers were male gender (P = 0.001), chronic neurologic disease (P = 0.015), chronic renal disease (P < 0.001) and nonsteroidal anti-inflammatory drug consumption (P = 0.035). Exposure factors for duodenal ulcers were H. pylori infection (P < 0.001) and steroid consumption (P = 0.031). Chronic renal disease was the only independent factor associated with gastric erosions (P = 0.026), those associated with duodenal erosions being H. pylori infection (P = 0.023), active smoking (P = 0.006) and chronic arthritis (P = 0.008). No risk factor was identified in 97/202 (48.0%) cases. Conclusions:H. pylori remains a risk factor for duodenal, but not for gastric lesions in children in countries with low prevalence of infection. No risk factor could be identified in half of the children with gastro-duodenal ulcers/erosions.
Keywords: Helicobacter pylori; peptic ulcer disease; gastric and duodenal ulcer; gastric and duodenal erosions; children; CHILDHOOD PEPTIC-ULCER; DUODENAL-ULCERS; DISEASE; ETIOLOGY; COMMON